1998
DOI: 10.1093/ageing/27.2.137
|View full text |Cite
|
Sign up to set email alerts
|

A kinematic comparison between elderly and young subjects standing up from and sitting down in a chair

Abstract: There is a relationship between changes in the motor control of the task, which appeared during periods of potential postural instability, and the effects of ageing on postural stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
1
5

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(74 citation statements)
references
References 0 publications
5
56
1
5
Order By: Relevance
“…They reported in their study that the transition type (i.e., SiSt or StSi) and the TD were not different. These results are at variance with reports from Mourey et al who, with different methodology, reported that the SiSt TD was greater than the StSi TD for both younger (22.8 ± 1.5 yr) and older (73.2 ± 5.5 yr) subjects [25]. Both studies, however, tested only a limited number of transitions under laboratory conditions.…”
Section: Subjectcontrasting
confidence: 77%
“…They reported in their study that the transition type (i.e., SiSt or StSi) and the TD were not different. These results are at variance with reports from Mourey et al who, with different methodology, reported that the SiSt TD was greater than the StSi TD for both younger (22.8 ± 1.5 yr) and older (73.2 ± 5.5 yr) subjects [25]. Both studies, however, tested only a limited number of transitions under laboratory conditions.…”
Section: Subjectcontrasting
confidence: 77%
“…This decrease has a physiologic basis in aging and is amplified by disuse and dysfunction. In general, aging adults demonstrate decreases in movement speed (Light, 1990;Mankovsky, Mints, & Lisenyuk, 1982;Poston et al, 2008;Yan et al, 1998), accuracy of movement (Chaput & Proteau, 1996), reaction time (Light, 1990;Sparrow et al, 2006;Yan et al, 1998), strength (Roos et al, 1997;Vandervoort, 2002), hand dexterity (Contreras-Vidal, Teulings, & Stelmach, 1998;Seidler, Alberts, & Stelmach, 2002), and postural control (Jonsson, Henriksson, & Hirschfeld, 2007;Koceja, Allway, & Earles, 1999;Mourey et al, 1998;. En masse, these changes have the potential to contribute to a spiral of disuse and loss of function that often characterizes the process of aging.…”
Section: Changes To the Human Sensorimotor System Across The Lifespanmentioning
confidence: 99%
“…Generally, young and elderly subjects actually execute the sit-to-stand phase faster than the stand-to-sit phase [30,37]. This is most likely due to the lack of visual information for the control of the backward motion during stand-to-sit.…”
Section: Young and Elderly Subjects Presented Similar Behaviour Regarmentioning
confidence: 99%